Case Report of Latent Autoimmune Diabetes in Adults - misdiagnosed as type 2 Diabetes Mellitus - Todorova, Biljana; Jovanovska Mishevska, Sasha; Bitoska, Iskra; Bajraktarova Prosheva, Tatjana; Plasheski, Tosho; Milenkovikj, Tatjana (My University, 2022)
Introduction: Latent Autoimmune Diabetes in Adults (LADA) is a form of autoimmune mediated diabetes in adults and a hybrid form of diabetes with features of both type 1 (T1DM) and type 2 diabetes (T2DM). The diagnosis of LADA according to Immunology of Diabetes Society is based on three features: age over 35, Presence at least one of four autoantibodies to pancreatic islet cell antigens and insulin independance at least 6 months after diagnosis. Unfortunately, patients with LADA are often misdiagnosed as having T2DM, shows a sustained poor glycemic control over time and significantly increased risk of microvascular complications. CASE REPORT: We present a fimale patient aged 52. She was diagnosed as T2DM when she was 36. Her past history includes: Rheumatoid Arthritis, family history-son and father diagnosed with type T1DM at the age of 26 and 33 years, respectively. She was treated with basal insulin therapy for seven years and due to poor glycaemic control the therapy was intensified. Several months before the admittance toour hospital she had have a history of frequent urination and hypoglicemic episodes followed by loss of consciousness. Laboratory revealed: HbA1c- 8.03% ; C- peptide 0,314ng/ml (0,53-2,9 ng/ml. The rest of the laboratory was normal. Ophthalmology exam stressed non-proliferative retinopathy. Immunologic analyses revealed positive Glutamic Acid Decarboxylase Autoantibodies (GADA) 65 and Insulin Autoantibodies (IAA). DISSCUSION: Our patient was diagnosed and treated as T2D for 15 years. The susspision for LADA was raised during her last exam. In our patient, there were two antibodies found out of four-GADA65 and IAA. She was already on insulin therapy and there was no need major change of the insulin therapy. CONCULION: Prevalence of LADA is increased in the patients with family history of T1DM. The early recognition of LADA is of utmost importance. Recognizing LADA at early stage will lead to early initiation of insulin, better glycemic control as well as the preservation of residual beta-cell function in adult-onset autoimmune diabetes.